Ja wiem, że to przedmowa - Poprawa, Adam (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
Stanisław Barańczak’s collection I Know It’s Not Right (Ja wiem, że to niesłuszne), published as samizdat in 1978, included a preface by Adam Michnik. The article analyses this preface and attempts to determine its addressee and understand the author’s intentions.